Central corneal thickness in spectral-domain OCT and associations with ocular and systemic parameters - Schuster, Alexander K.; Fischer, Joachim E.; Voßmerbäumer, Urs (Journal of ophthalmology, 2016)
Background. Optical coherence tomography (OCT) allows quantitative analysis of the anterior segment of the eye with a noncontact examination. The aim of this study is to analyze associations of central corneal thickness (CCT) as measured by OCT with ocular and systemic cardiovascular parameters. Methods. A cross-sectional study of 734 persons was performed in a working age population. Only healthy eyes were included. A comprehensive ophthalmological examination including refraction, noncontact tonometry, and imaging of the anterior segment by SD-OCT was performed. In parallel, a broad range of systemic cardiovascular parameters were measured. Associations were analyzed using a generalized estimating equations’ model. Results. CCT measurements showed a significant association with corneal curvature and intraocular pressure: a thinner CCT was associated with a flatter cornea and with lower intraocular pressure (). Age was positively associated with CCT (); all other cardiovascular parameters were not associated. Conclusion. A thinner cornea is associated with a flatter surface and with lower intraocular pressure readings, while there are no independent associations with refraction and systemic cardiovascular parameters. Our findings highlight the value of SD-OCT CCT measurements as a standard tool in anterior segment analysis.
Gesehen am 19.02.2019